THE CROHN DISEASE OF THE EUSOPHAGUS - Coşkun TECİMER; Nedim KIZILKAYA; Ramazan ÖZDEMİR; Onur AKIN; Egemen TAYFUN; Hüseyin ÜSTÜN; Fatih HİLMİOĞLU; Mehmet YÜCESOY (Turkish Journal of Gastroenterology, 2020)
-